BCL2 and P53 immunoexpression in colorectal carcinoma - Abdulhameed, Tenya Tariq; Ali, Salah Abubakir (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: The products of BCL2 and P53 genes are involved in the regulation of proliferation and apoptosis and have been associated with prognosis in several malignancies, including colorectal carcinoma. This study aimed to investigate the expression of antiapoptotic BCL2 protein in colorectal carcinoma and to examine its association with one of the important mediators of apoptosis (P53 protein) and with clinicopathological factors, and to assess the prognostic value of the combined BCL2 /P53 phenotypes by studying their relation with the two most important prognostic factors of grading and staging. Methods: A retrospective and prospective study was carried out from the period of August 2010 to June 2011. Sixty eight formalin-fixed, paraffin-embedded blocks of colorectal carcinoma cases were evaluated regarding BCL2 expression, P53 nuclear accumulation and their concomitant expression using immunohistochemistry by Dako Cytomation.LSAB + System-HRP. Results: The study shows that 29.41% of the colorectal tumors were positive for BCL2 protein expression and associated with earlier stage tumors (P = 0.021), while 72.06% were positive for P53 protein expression and associated with later stage tumors (P = 0.006) and male gender (P = 0.005). There was a trend toward an inverse correlation between BCL2 and P53 expression (P = 0.0013). Tumors that did not express detectable levels of BCL2 but exhibited nuclear accumulation of P53 were most common and associated with later stage tumors (P = 0.003). Conclusion: Concomitant assessment of both BCL2 and P53 status may be valuable in predicting the aggressiveness of tumors in patients with colorectal carcinomas.